PENGARUH DRAINASE HORIZONTAL PADA STABILITAS LERENG DENGAN METODE ELEMEN HINGGA - Upomo, Togani Cahyadi; Kusumawardani, Rini; Nugroho, Untoro (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2018)
The horizontal drains have been commonly used for slope stabilization. The effects of the horizontal drain analyzed by finite element method and the slope stability is evaluated by the global safety factor using simplified bishop method. The conclusions are obtained : firstly, the horizontal drains can more effective for lower the water table and increase the safety factor; second, the length of horizontal drains influence of the safety factor. The longer of horizontal drain can increase the safety factor. Keywords: safety factor, horizontal drain, slope stability